Translation Shift Analysis of ANTARA News - Putri, Vania Mendoza; Hamzah, Hamzah (English Language and Literature, 2021)
Many research of translation shift analysis has been studied, but it is not common to find translation shift analysis approach in analysing online news. The study is aimed to analyze the types of translation shift in the Indonesian – English translation in ANTARA News. Translation shift is the alteration of lexicogrammar in source language occurred when a translator is translating a text in order to get the equivalent meaning in the target language. There are two types of translation shift introduced by Catford (1965): level shift and category shifts (structure shift, class shift, unit shift, intra-system shift). The research applied descriptive qualitative methodology. The research focused on finding out the types translation shifts that occurred in the ANTARA News. The data in this research are five selected news reported about COVID-19 in Indonesia, collected by browsing official website of ANTARA News both in Indonesian and English versions. The news that is being studied in this research applied the theory of translation shift by Catford (1965), and the utterances are the source of the data, as Indonesian is the source language (SL) and another as an English the target language (TL). The data are saved in the table of indicators in the format of Microsoft Word. After finishing the analysis, it was found out that there are 76 shifts in ANTARA News with five categories. Level shift appeared 4 times, structure shift appeared 31 times, class shift appeared 14 times, unit shift appeared 21 times, and intra-system shift appeared 6 times. In conclusion, it does not rule out the possibility that translation shift can still appear in non-fiction text such as online news, due to the difference between the languages in many aspects such as linguistic feature, cultural background, and grammatical form.